Accumulation and transport of atmospherically deposited PFOA and PFOS in undisturbed soils downwind from a fluoropolymers factory - Thomas Gerardu; Joris Dijkstra; Henry Beeltje; Alex van Renesse van Duivenbode; Jasper Griffioen (Environmental Advances, 2023)
PFOA and PFOS are widely found PFAS components in Dutch topsoils. PFOA was emitted to the atmosphere during 1970-2012 from a fluoropolymers factory, and was deposited mainly within a radius of 50 km. For the first time, detailed concentration-depth profiles of PFOA and PFOS were measured in undisturbed soils downwind of the factory. Three locations were selected with about 3 meters of sand soil and free infiltration of rain. An adjacent peat soil was selected for comparison. In the sand soils, concentration-depth profiles of PFOA showed a distinct bell-shaped pattern with the highest contents at 0.2-0.5 m below surface, and lower contents both at the surface and at further depth (up to 3.5 m below surface). This observation indicates that the highest atmospheric deposition has passed, and that PFOA gradually migrates towards groundwater. Concentrations of PFOS are highest near the surface and reach the detection limit at 1 m below surface, suggesting that its downward migration occurs much slower. HYDRUS was used to model PFAS transport in the vadose zone assuming steady-state infiltration. The PFOA depth profiles in the sand soils can be described assuming plausible historic, atmospheric emission of PFOA from the factory and Koc values within the literature range. However, the retention observed must be attributed to linear partitioning between water and both soil organic matter and the air-water interface. Somewhat stronger retention holds for PFOS, but PFOS cannot originate from the factory in the extent found. An alternative explanation is historic, rather parallel emissions from nearby sources such as waste incinerators. Based on measurements and modelling, this study illustrates that PFOA, and to a lesser extent PFOS, should not be treated as immobile contaminants in topsoil as is currently the case in Dutch soil policy, but rather as mobile contaminants of which the legacy amounts in soil will pollute groundwater for many decades.